The child body and the adult body in research with children (Práxis Educativa, 2025)
Through an investigation conducted from 2018 to 2020, aimed at understanding children’s perspectives on their experience transitioning from Early Childhood Education to the early grades of Elementary School, this text presents the concept of the child body in relation to the adult body in research with children. The research was carried out in two educational institutions: a Municipal Center for Early Childhood Education and a school for the early grades of Elementary Education, located in Ponta Grossa, state of Paraná, Brazil. It used a qualitative approach with an ethnographic interpretative framework and adapted data collection tools to the investigation contexts: participant observation, individual interviews, and monitored visits. Drawing from the theoretical approach of Childhood Sociology, which views the child body as a competent, creative subject and culture producer, this article aims to broaden the reflection on the concepts of the child body and the adult body, supporting the legitimacy of children’s voices and their varied forms of participation in educational research contexts. The research yielded some results and reflections, such as the finding that children enjoy and welcome changes inherent to their school contexts; and that the child body, as they move from Early Childhood Education to the early grades of Elementary School, is both a space for their experiences, and a space for their interpretations and social actions. Through this investigation, the position of less adult is advocated as an ethical way of relating the adult body and the child body in the data production process when conducting research with children.Keywords: Child body. Adult body. Research with children. Less adult.